(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the stages of formation and development of education of children with visual impairments from a historical and pedagogical perspective. In the course of the research, the development of educational institutions for children with visual impairments, special pedagogical approaches and typhlopedagogy in world and national education systems is highlighted. Also, the evolution of ideas, methods and didactic principles aimed at ensuring the right of children with visual impairments to education based on historical sources is analyzed.